Mode Splitting Based on Polarization Manipulation in Few-Mode Fiber - Lee, Yen Sian; Lim, Kok Sing; Zaini, Muhammad Khairol Annuar; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2018)
We report a mode splitting technique for LP01 and LP11 modes based on polarization manipulation in a few-mode fiber (FMF) by using a three-paddle two-mode fiber polarization controller (TMPC). In the characterization test, LP01 and LP11 modes are simultaneously excited in a two-mode fiber (TMF) based on core-offset splicing technique. By employing the TMPC, the LP01 and LP11 modes in the TMF are aligned into two perpendicular polarization states and then separated by a polarizing beam splitter (PBS). The output LP01 and LP11 modes from the PBS have high mode extinction ratio (>30 dB), good power stability (≤0.5 dB), and stable mode profile position over the wavelength range of 1530-1560 nm (C -band). The proposed technique is a simple and efficient method for mode manipulation and management in various space-division multiplexing applications.